'It's not over when it's over': persistent neurobiological abnormalities in recovered depressed patients. - Bhagwagar, Z; Cowen, P (2008)
The tendency of major depression to recur is a leading problem in clinical management and is responsible for much of the illness burden. Until recently, biological studies of depression have focused on the mechanisms involved in acute illness but there are now many data to suggest that neurobiological abnormalities persist when depressed patients are clinically recovered and withdrawn from medication. These abnormalities encompass a number of neurochemical and neuropsychological mechanisms that could be relevant to recurrence, including changes in the availability of serotonin (5-hydroxytryptamine, 5-HT) receptor subtypes, decreases in cortical gamma-aminobutyric acid (GABA), increases in cortisol secretion and negative biases in the processing of emotional information. Studies of groups at high risk of depression before illness onset will help to clarify which biological abnormalities precede the development of depression and which are the product of recurrent illness. Ultimately this work should lead to a better understanding of the neurobiology of vulnerability to depression and more innovative approaches to primary and secondary prevention.